운동선수들을 위한 예방접종 근거와 추천 - 오범조; Bumjo Oh; 이영구; Young Koo Lee; 정부윤; Booyoon Cheung; 이경태; Kyung Tai Lee; 하철원; Chul-won Ha (대한스포츠의학회지, 2019)
As interest in sports rapidly grows in Korea, fostering of elite athletes and preservation of the athletic ability no longer became the task of advanced countries only. In that aspect, health of athletes and their associated coaches, athlete trainers, team members such as team doctors, and even their families is certainly a matter of concern. Especially when it comes to the inoculation of infectious disease prevention, it needs to be considered as one of the most economical and effective ways to promote health in sports people as well as elite athletes. The purpose of this article is to go over the specific circumstances of the athletes and related literatures on vaccination. In addition, we provide recommendations on the vaccination of athletes regarding the actual situation of sports in Korea.